The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.ijindorg.2007.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Strategic incentives for market share

Abstract: Market share objectives are prominent in many industries, especially where managers pay much attention to league table rankings. This paper explores the strategic rationale for giving managers incentives based on market share, motivated by evidence from executive compensation practice in the automotive and investment banking industries. Strategic incentives for market share dominate the well-known sales revenue contracts analyzed in much of the literature, but perhaps surprisingly also lead to less competitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 24 publications
0
88
1
3
Order By: Relevance
“…Taking this fact into account, we should reformulate the model and examine the robustness of this result with respect to both foreign firms and the differentials of each firm's cost. As the third extension of our paper, we should examine whether the above result is robust against the assumption that each firm adopts other delegation regimes, for example, the market share delegation case presented in Jansen et al (2007) and Ritz (2008) and the relative performance case in Miller and Pazgal (2001). These issues are left for future research.…”
Section: Resultsmentioning
confidence: 91%
“…Taking this fact into account, we should reformulate the model and examine the robustness of this result with respect to both foreign firms and the differentials of each firm's cost. As the third extension of our paper, we should examine whether the above result is robust against the assumption that each firm adopts other delegation regimes, for example, the market share delegation case presented in Jansen et al (2007) and Ritz (2008) and the relative performance case in Miller and Pazgal (2001). These issues are left for future research.…”
Section: Resultsmentioning
confidence: 91%
“…Yet, there is evidence suggesting that CEO compensation is linked with own market share (Peck, 1988;Borkowski, 1999). Ritz (2008) and Jansen et al (2007) formalize contracts combining own profits and own market share. Thus, an interesting direction for future experimental research could be to expand the firms owners' strategy space by allowing them to compensate their managers with contracts combining own profits and own market share as well.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies on average revealed a significant positive correlation between these variables (Szymanski et al, 1993). But recent empirical results suggest that the relation between these two depends on competitive and strategic context and the fabricated or erroneous impacts that form a great part of the criteria used for measuring this relation (Ritz, 2008).…”
Section: Roe=net Income Margin X Equity Turnovermentioning
confidence: 96%